A novel combination of enzymatic hydrolysis and microbial fuel cell for electricity production from bakery waste. (February 2020) - Han, Wei; Liu, Yanxu; Xu, Xiaobin; He, Hong; Chen, Long; Tian, Xiaoqing; Hou, Pingzhi; Tang, Junhong
Highlights: A novel bioprocess for electricity generation from bakery waste was developed. The power density reached a peak value of 29.96 mW/m 2 . High-starch containing raw materials could be directly used for electricity generation. Abstract: This work developed a novel two-stage bioprocess for electricity generation from bakery waste (BW). In the first stage, commercial glucoamylase was utilized to hydrolyze the BW to produce soluble BW hydrolysate. It was found that 100 g BW could be converted to 32 g hydrolysis solid and 760 mL BW hydrolysate. The highest glucose production of 21.9 g/L could be achieved within 5 h. In the second stage, the soluble BW hydrolysate was utilized as feedstock for electricity generation in microbial fuel cell (MFC). The maximum voltage of 0.386 V was obtained. The power density reached a peak value of 29.96 mW/m 2 when the external resistance was 1090 Ω. It could be potentially utilized to transform high-starch containing raw materials into biofuels production which could reduce the cost of biofuels production effectively for industrial application.